Pengaruh Harga Sawit dan Produktivitas Terhadap Pendapatan Petani Kelapa Sawit di Desa Pir Trans Sosa II Kecamatan Hutaraja Tinggi Kabupaten Padang Lawas Sumatera Utara - Shima; Afrijal; Sherliyana Anggraini (PT. Hasba Edukasi Mandiri, 2025)
The purpose of this study was to determine the effect of palm oil price and productivity on the income of palm oil farmers in Pir Trans Sosa II Village, Hutaraja Tinggi District, Padang Lawas Regency, North Sumatra. The sample in this study was taken using the slovin formula, namely 75 observed samples. The data analysis technique used is descriptive analysis, multiple linear regression analysis and hypothesis testing with the help of a computer program, namely SPSS (Statistical Package For Social Science) 25. The results of this study can be seen that the price of oil palm partially has a significant effect on farmers' income, productivity partially has no significant effect on farmers' income, price and productivity together have a significant effect on Farmer income.